Representations of Resistance: The RCMP and C-IRG's Representations of Indigenous Land Defenders' Dissent Against the Coastal GasLink Pipeline on Wet'suwet'en Territory - Prashad, Nicolette (Université d'Ottawa / University of Ottawa, 2025)
A global uptick in both the frequency and scale of protests has led to increased visibility surrounding the policing of protests, particularly in Canada. Recent high-profile Indigenous demonstrations such as the Idle No More movement, Fairy Creek protests, and resistance against the Coastal GasLink and TransMountain Pipelines have significantly increased public scrutiny about the RCMP's role in policing Indigenous resistance. This thesis will examine how the RCMP (and more specifically, C-IRG) represented Indigenous land defenders during the Wet'suwet'en opposition to the Coastal GasLink pipeline. This study employs a qualitative, critical content analysis of RCMP documents obtained through access to information and privacy (ATIP) requests using a theoretical framework of settler colonial theory to provide insight into the varied and complex ways in which the RCMP represents Indigenous resistance on Wet'suwet'en territory. This study finds that land defenders on Wet'suwet'en territory are represented as threats to Canadian law, police officers, infrastructure projects and workers, and even to themselves. These representations demonstrate that the founding logics of settler colonialism actively persist today, continuously re(created) through mechanisms such as the RCMP's policing of Indigenous resistance. Ultimately, these findings suggest that the RCMP's representations of Indigenous land defenders go significantly beyond the scope of their policing duties by emphasizing their perceived threat of a militaristic, occupying force of land defenders who jeopardize the Canadian state's and private corporations' access to the land, its resources, and by extension, capital.
Keywords: policing; land defence; Indigenous; settler colonialism